Understanding the Nature of Participatory Action Research in Health - Joel Rey Ugsang Acob; Heru Santoso Wahito Nugroho (Health Notions, 2019)
Not until one has understand and fully realized that participatory action research is less objective that any other shapes of scientific investigation, the conduct of such process remains mysterious and difficult to achieve. This article is aimed at bridging myths in cultivating community of people with facilities of identifying their current stance, investigating their own practices, and able to address the problem to transform them under the limelight of experts. Moreover, the manuscript includes discussions on the nature, dimension and frameworks of participatory action research activity to improve situation, reflect and act again until they see transformation in process through synergistic exertions between those involved. Keywords: action research; participatory action research; caring; research; nursing